Genetic effects of background-independent loci for grain weight and shape identified using advanced reciprocal introgression lines from Lemont x Teqing in rice - Zheng, T.Q.; Wang, Y.; Ali, A.J.; Zhu, L.H.; Sun, Y.; Zhai, H.Q.; Mei, H.W.; Xu, Z.J.; Xu, J.L.; Li, Z.K. (Wiley, 2011)
Genetic background effect and environmental sensitivity are two major obstacles for marker‐assisted breeding (MAB) of complex traits. Background‐independent (BI) loci for 1000‐grain weight (TGW) and grain shape (GS) were detected over three seasons using a set of reciprocal introgression lines (ILs) from Lemont × Teqing cross with parents having distinctive GS but equal TGW. Reciprocal ILs in advanced (F11–13) generations were genotyped using 142 polymorphic simple sequence repeat (SSR) markers on 64 chromosome bins. Nineteen bins of BI loci significantly associated with TGW and/or GS that were identified consistently over multiple seasons and additive effects were in the opposite directions at the same loci between two backgrounds. These 19 bins could be classified into three types: Type I includes four genetic overlapping bins affecting both TGW and GS, Type II includes nine genetic overlapping bins controlling GS component traits, and Type III includes six bins for single GS component. Among them, five stably expressed BI loci (bins 2.2, 2.5, and 3.7 for grain length [GL] and bins 5.2 and 7.4 for grain width [GW]) found consistently over three seasons would be the first choice for MAB. Secondary choice would be the loci that expressed over at least over two seasons and include bins 1.2, 3.3, 4.3 for GL and bins 7.1 and 11.5 for GW. Two related key traits, one for yield (TGW) and the other for grain quality (GS), can now be fully utilized through marker‐aided transfer or pyramiding of the identified BI loci in rice (Oryza sativa L.) improvement programs.